Generalizations of semicoprime preradicals - Darani, A.Y.; Mostafanasab, H. (Algebra and Discrete Mathematics, 2016)
This article introduces the notions quasi-co-n-absorbing preradicals and semi-co-n-absorbing preradicals, generalizing the concept of semicoprime preradicals. We study the concepts quasi-co-n-absorbing submodules and semi-co-n-absorbing submodules and their relations with quasi-co-n-absorbing preradicals and semi-co-n-absorbing preradicals using the lattice structure of preradicals.